Studies on Genetic Variability and Character Association in Chilli Genotypes (Capsicum annuum L.) - Sakshi Singh; A. K. Joshi; Amit Vikram; Sandeep Kansal; Sudha Singh (International Journal of Economic Plants)
The present investigation was carried out at Experimental Farm of Regional Horticultural Research and Training Station Dhaulakuan, District Sirmour (HP), Dr. YS Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, during Kharif season, 2018 to ascertain extent of variability, heritability and genetic advance as percentage of mean for yield and other horticultural traits of 21 chilli genotypes. The experiment was laid out in RCBD with three replications at spacing of 45cm × 45cm. Analysis of variance indicated significant differences among the genotypes for all the traits studied.  RACH-132 exhibited the maximum number of fruits per plant (97.27), fruit weight at edible maturity (4.08 g), green fruit yield plant-1 (280.10 g), red fruit yield plant-1 (275.89 g) and fruit diameter (1.23 cm) while, number of seeds and thousand seed weight was maximum in RACH-121 (100.40, 5.12 g). DKC-8 (0.49%) recorded the maximum capsaicin content. The estimates of phenotypic and genotypic coefficients of variation (PCV and GCV) were moderate to high for all characters studied except days to first red maturity. High heritability coupled with high genetic gain was found for characters like green fruit yield plant-1, red fruit yield plant-1 and capsaicin content which indicates that these characters were under the strong influence of additive gene action and hence simple selection based on phenotypic performance of these traits would be effective.